Teori Belajar Erickson Pada Pembelajaran Kooperatif Tipe Jigsaw Untuk Meningkatkan Motivasi Belajar Peserta Didik Kelas III di SD Muhammadiyah 2 Manado - Fitriani Fitriani; Maemonah Maemonah (Latifah Pres, 2021)
This study aims to increase the learning motivation of students. This study uses an experimental method with quantitative research type. The data collection techniques used were interviews and questionnaires, the subjects of which were educators and students. Data analysis was performed by reducing data, displaying data and drawing conclusions. The results showed that using a cooperative model in learning was able to make students more active, generate cooperation, express opinions and provide opportunities to ask questions so that students feel motivated to carry out learning in school and it is proven by the following results: Activity / Student Motivation 64.28% and after using the cooperative model it became 92.85%, and the average completeness of learning before using the cooperative model was 70.71, after using the cooperative model 95.71 and classical completeness before using the cooperative model 64.28% after using the cooperative model reached 92, 85% of these data indicate that the use of cooperative models can increase student motivation.